Electronic Development of Local Content-Based Citizenship Education Course Modules in South Sumatra - Hamzah, Amir; Nurlaeli, Nurlaeli; Febriani, Aulia Rizki; Saputra, Isnainun Wahyu; Jadidah, Ines Tasya; Syarifuddin, Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The purpose of this research is to produce an electronic module with South Sumatra Local Content in Madrasah Ibtidaiyah Civic Education Course in PGMI FITK UIN Raden Fatah Palembang, develop a valid PKN Electronic Module, and develop a practical electronic module. The research method used is Research and Development, with the ADDIE model. The needs analysis data and trials were obtained from students. Data collection techniques through questionnaires, observations, and interviews. The subjects of this study were students and lecturers. Data analysis was carried out through data analysis of validation results and practicality data using a Likert Scale and Practicality Test. The results of the development carried out by electronic modules, namely Needs Analysis, Student Analysis, Curriculum Analysis and Material analysis so that Electronic Modules can be developed according to the needs of the Electronic Modules that have been designed and developed are validated by Material experts quantitatively and qualitatively so that the following results can be obtained, Construct Experts and Language Experts who get the following results Material 95%construct 81, 25%, linguists 94.4%, thus the model developed in the category is very valid, then tested practicality to small and large groups to see the practicality of the electronic module developed in the results for a small scale the average score of the validators of Language, Material and Media developed is categorized as very valid, and the practicality of the research developed with five categories are all categorized as practical.